Pemikiran Mehdi Golshani tentang Dialektika Agama dan Sains - Mukhlisin Saad (Teosofi: Jurnal Tasawuf dan Pemikiran Islam, 2016)
This article seeks to scrutinize Mehdi Golshani’s thought on dialectical relation of religion and science. In the history of human being, the relation of religion and science has been dynamically connected. Each side has correlated, dominated, and synergized with one to another. The relation of these two entities has brought about a number of various paradigms, namely theocentric, anthropocentric, and Theo-anthropocentric paradigms. Employing bibliographical approach, this study discusses historical relation of religion and science, which has been long connected since the Medieval Century. The study finds that Golshani has founded his conception of science on the basis of dichotomization between what so-called the sacred sciences and the secular one. He has tried to link these two entities by, among others, dialoguing between material aspect and supra-natural realm. To him, either religion or science shares a common orientation in order to reach the supreme truth, i.e. God. When religion undergoes the quest through obedience upon the dogmas stipulated by God, science prefers reason to get along with Him. In the meantime religion and science are able to integrate and share with each other. Golshani calls it the Islamic Sciences.